Inappropriate activation of the renin-angiotensin system improves cardiac tolerance to ischemia/reperfusion injury in rats with late angiotensin II-dependent hypertension - Husková, Zuzana; Kikerlová, Soňa; Miklovič, Matúš; Kala, Petr; Papoušek, František; Neckář, Jan (Frontiers in Physiology, 2023)
The aim of the study was to clarify the role of the interplay between hypertension and the renin-angiotensin system (RAS) in the pathophysiology of myocardial ischemia/reperfusion (I/R) injury. We hypothesized that in the late phase of hypertension with already developed signs of end-organ damage, inappropriate RAS activation could impair cardiac tolerance to I/R injury. Experiments were performed in male Cyp1a1-Ren-2 transgenic rats with inducible hypertension. The early phase of ANG II-dependent hypertension was induced by 5 days and the late phase by the 13 days dietary indole-3-carbinol (I3C) administration. Noninduced rats served as controls. Echocardiography and pressure-volume analysis were performed, angiotensins’ levels were measured and cardiac tolerance to ischemia/reperfusion injury was studied. The infarct size was significantly reduced (by 50%) in 13 days I3C-induced hypertensive rats with marked cardiac hypertrophy, this reduction was abolished by losartan treatment. In the late phase of hypertension there are indications of a failing heart, mainly in reduced preload recruitable stroke work (PRSW), but only nonsignificant trends in worsening of some other parameters, showing that the myocardium is in a compensated phase. The influence of the RAS depends on the balance between the vasoconstrictive and the opposed vasodilatory axis. In the initial stage of hypertension, the vasodilatory axis of the RAS prevails, and with the development of hypertension the vasoconstrictive axis of the RAS becomes stronger. We observed a clear effect of AT1 receptor blockade on maximum pressure in left ventricle, cardiac hypertrophy and ANG II levels. In conclusion, we confirmed improved cardiac tolerance to I/R injury in hypertensive hypertrophied rats and showed that, in the late phase of hypertension, the myocardium is in a compensated phase.